Influence of Voids Ratio on Impact Behavior of Circular Ferrocement Slabs - Muyasser M. Jomaah; Muna Zead Baraa (Civil Engineering Journal, 2019)
The objective of using materials is to fully utilize the properties of these materials in order to obtain the best performance of the structure. The merits of material are based on many factors like, workability, structural strength, durability and low cost. Ferrocement is an excellent construction system. This paper studies the behavior of ferrocement circular slabs under impact load. The experimental program include testing four sime fixed supported ferrocement circular slabs of 800mm diameter and 50mm thickness. The Influence of the use of styropor voids was investigated in different ratios (24% and 48%) and a number of wire mesh layers four and six layers. Impact load test results revealed that increasing number of wire mesh from 4 to 6 led to an increase in the impact energy for first crack by (41.991% ,37.62%) respectively when using voids ratio by (24% and 48%) respectively and impact energy for full perforation by (21.7% and 9.94%) respectively when using voids ratio by (24% and 48%) respectively. Ferrocement circular slabs are used in construction fields such as roofs, tanks, manholes, etc.